2002
DOI: 10.1038/nature01242
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of synaptic plasticity triggered by selective suppression of activity in individual neurons

Abstract: The rules by which neuronal activity causes long-term modification of synapses in the central nervous system are not fully understood. Whereas competitive or correlation-based rules result in local modification of synapses, homeostatic modifications allow neuron-wide changes in synaptic strength, promoting stability. Experimental investigations of these rules at central nervous system synapses have relied generally on manipulating activity in populations of neurons. Here, we investigated the effect of suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
406
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(443 citation statements)
references
References 30 publications
32
406
3
2
Order By: Relevance
“…To address such a possibility, one would need to block either activity or neurotransmission, but not both. Recent studies have demonstrated that neither hyperpolarization nor reducing spike rate in the postsynaptic cell leads to compensatory changes in mPSC amplitude as would be predicted by the cell activity model (8,(16)(17)(18)(19). In those studies, the release and binding of neurotransmitters to their receptors was not altered, and thus the results are consistent with the neurotransmitter model.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…To address such a possibility, one would need to block either activity or neurotransmission, but not both. Recent studies have demonstrated that neither hyperpolarization nor reducing spike rate in the postsynaptic cell leads to compensatory changes in mPSC amplitude as would be predicted by the cell activity model (8,(16)(17)(18)(19). In those studies, the release and binding of neurotransmitters to their receptors was not altered, and thus the results are consistent with the neurotransmitter model.…”
supporting
confidence: 75%
“…Once GABA A transmission is no longer depolarizing, it may not be able to trigger the same downstream cascades, and the role of triggering compensatory quantal changes may be transferred to AMPAergic transmission. In four separate studies (in vitro and in vivo), activity was reduced in only the postsynaptic cell by expression of a potassium channel, whereas neurotransmitter release by the cell inputs remained intact and presumably unaltered (16)(17)(18)(19). Although some of these studies reported a compensatory change in probability of release, none of them observed the expected increase in quantal amplitude.…”
Section: Discussionmentioning
confidence: 92%
“…The PCR product was inserted into the pCAGGS vector. To generate nonconducting kir2.1 mutant, the pore-region amino acid motif GYG was mutated to AAA (16). Cotransfection of pCAGGS-eyfp and pCAGGS-kir2.1 (or pCAGGS-kir2.1 mutant) was performed for organotypic coculture preparations to examine the detail of axon morphology.…”
Section: Methodsmentioning
confidence: 99%
“…To do this, neural activity of either thalamic or cortical cells was selectively silenced by means of overexpression of Kir2.1, an inward rectifying potassium channel (16,17). Our findings suggest that TC axon branching is inhibited by reducing the activity at either of these locations, suggesting that both pre-and postsynaptic activity is required for the development of TC axon branching.…”
mentioning
confidence: 96%
“…Experiments have consistently shown that increased neuronal activity, produced by chronic disinhibition, results in diminished glutamatergic synaptic transmission (Turrigiano et al, 1998;O'Brien et al, 1998;Watt et al, 2000). However, with few exceptions (Desai et al, 2002;Burrone et al, 2002;Wierenga et al, 2006) these studies were not explicitly designed to determine the impact of persistent hyperexcitability on neuronal growth and maturation.…”
Section: Neuronal Activity and Dendrite Growthmentioning
confidence: 99%